All-atom molecular dynamics simulations of the combined effects of different phospholipids and cholesterol content on electroporation. Issue 38 (30th August 2022) - Guo, Fei; Wang, Ji; Zhou, Jiong; Qian, Kun; Qu, Hongchun; Liu, Ping; Zhai, Shidong
Abstract : In this paper, we applied all-atom molecular dynamics (MD) simulations to study the effects of phospholipids and cholesterol content on bilayer membrane electroporation. Abstract : The electroporation mechanism could be related to the composition of the plasma membrane, and the combined effect of different phospholipid molecules and cholesterol content on electroporation has rarely been studied nor conclusions drawn. In this paper, we applied all-atom molecular dynamics (MD) simulations to study the effects of phospholipids and cholesterol content on bilayer membrane electroporation. The palmitoyloleoylphosphatidylcholine (POPC) model, palmitoyloleoylphosphatidylethanolamine (POPE) model, and a 1 : 1 mixed model of POPC and POPE called PEPC, were the three basic models used. An electric field of 0.45 V nm −1 was applied to nine models, which were the three basic models, each with three different cholesterol content values of 0%, 24%, and 40%. The interfacial water molecules moved under the electric field and, once the first water bridge formed, the rest of the water molecules would dramatically flood into the membrane. The simulation showed that a rapid rise in the Z -component of the average dipole moment of the interfacial water molecules ( Z -DM) indicated the occurrence of electroporation, and the same increment of Z -DM represented a similar change in the size of the water bridge. With the same cholesterol content, the formation of the first water bridge was the most rapid in the POPC model, regarding the average electroporation time ( t ep ), and the average t ep of the PEPC model was close to that of the POPE model. We speculate that the differences in membrane thickness and initial number of hydrogen bonds of the interfacial water molecules affect the average t ep for different membrane compositions. Our results reveal the influence of membrane composition on the electroporation mechanism at the molecular level.